2006
DOI: 10.1177/0013124506291783
|View full text |Cite
|
Sign up to set email alerts
|

Peer Influences on the College-Going Decisions of Low Socioeconomic Status Urban Youth

Abstract: The roles that peers play in the decision to go to college are not well understood. Logistic regression is used to explore the role that peers play in the college-going decisions of a sample of low-income urban minority public high school graduates drawn from the National Education Longitudinal Study (NELS:88) database. Friends' plans are found to be the single best predictor of 4-year college enrollment for these low-income urban minority students, even when controlling for variables traditionally assumed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 17 publications
0
60
0
1
Order By: Relevance
“…Another, related benefit of participating in social networking that Greenhow and Burton () describe is peer feedback. Numerous studies have documented the significant influence of peers on underrepresented students’ postsecondary education plans (Holland, ; Perna & Titus, ; Sokatch, ; Wohn et al., ). In his study on the college‐going decisions of low‐income urban minority students, Sokatch () found that friends’ plans were the single best predictor of 4‐year college enrollment.…”
Section: Social Media and Students’ College Admission Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Another, related benefit of participating in social networking that Greenhow and Burton () describe is peer feedback. Numerous studies have documented the significant influence of peers on underrepresented students’ postsecondary education plans (Holland, ; Perna & Titus, ; Sokatch, ; Wohn et al., ). In his study on the college‐going decisions of low‐income urban minority students, Sokatch () found that friends’ plans were the single best predictor of 4‐year college enrollment.…”
Section: Social Media and Students’ College Admission Processmentioning
confidence: 99%
“…Numerous studies have documented the significant influence of peers on underrepresented students’ postsecondary education plans (Holland, ; Perna & Titus, ; Sokatch, ; Wohn et al., ). In his study on the college‐going decisions of low‐income urban minority students, Sokatch () found that friends’ plans were the single best predictor of 4‐year college enrollment. In addition to friends’ plans, peer group expectations for group members can exert a positive pressure to pursue higher education opportunities (Holland, ; Perna & Titus, ; Sokatch, ; Wohn et al., ).…”
Section: Social Media and Students’ College Admission Processmentioning
confidence: 99%
“…While it is unclear if there are socioeconomic differences in the influence of peers on college-going behavior, evidence suggests that peers may be more important for those who lack support elsewhere, such as low-income urban minorities and those whose parents have no college education (Choy, Horn, Nunez, & Chen, 2000;Sokatch, 2006). Indeed, if low-income or firstgeneration students are not exposed to high educational expectations or academic orientations at home, it could be hypothesized that peers play an even more important role in providing that positive influence.…”
Section: Frog-pond Perspectivementioning
confidence: 99%
“…Second only to parents, peers play a particularly large role in college readiness and are highly infl uential during the developmental period that coincides with the traditional high school years (Sokatch, 2006). e peers with whom students most frequently come into contact strongly aff ect school success (Coleman and others, 1966;Crosnoe, 2000).…”
Section: Peersmentioning
confidence: 99%